Analisa FRF secara teoritik dan eksperimental pada komponen struktur dengan profil pelat aluminium akibat eksitasi kejut dan random - Arman, R. (Universitas Mataram, 2020)
The dynamic behaviour of the vibration system in the experimental analysis is observed from the response to the stimulus acting on it. In this case, the relationship between the stimulus at a certain location and direction is specifically related to its response respectively. The relationship between stimulus and response is called the Frequency Response Function (FRF) or better known as the transfer function. In measuring the transfer function, the stimulus to the structure is given in the form of an excitation force while the vibration response measurement depends on the type of sensor or transducer used. Diverging from the above problems, vibration testing is carried out on a structural model. This test uses an Aluminum beam as a specimen by using an excitation signal that comes from an exciter and an impact hammer. This research aims to examine the dynamic response in the form of vibration characteristics response in the frequency spectrum of an Aluminum beam. Based on this spectrum maps, we can observe the dominant frequency (a frequency with large amplitude). Furthermore, from these frequency data, it is expected to determine which frequency components are derived from component element defects and indications of resonance frequencies on machine elements or noise originating frequencies.